Psychometric properties of Turkish online shopping addiction scale - Yılmaz, Tuğba; İkiz, Gizem and Avcı, Furkan Mertcan (Journal of Dependence, 2022)
Objective: Online behavioral addictions, one of the most important problems of today, are tried to be measured by researchers. The way people shop online and their attitudes are also explored in this context. In this study, it is aimed to carry out the Turkish translation, adaptation, validity and reliability studies of the Online Shopping Addiction Scale (OSAS), a scale developed to measure online shopping addiction. Method: During this study, measurements were carried out in two different time periods with a one-month interval. First of all, Online Shopping Addiction Scale (OSAS), Compulsive Online Buying Scale and Young Internet Addiction Scale-Short Form were applied to 324 participants. In the second measurement, the Online Shopping Addiction Scale was applied to 110 participants who participated in the first measurements. Results: It was found that the Turkish version of the CABÖ, which was originally a six-factor scale, gathered in five factors by combining the first two factors (significance and tolerance). The internal consistency coefficient of the scale was found to be .92, and the test-retest reliability was found to be .79. It was found that the internal consistency coefficients of the five sub-factors of the scale ranged from .40 to .88. The concurrent validity of the OSAS was tested with the Young Internet Addiction Scale, the Short Form, and the Compulsive Online Buying Scale, and significant results were obtained. Conclusion: The results of the study show that the Turkish version of Online Shopping Addiction Scale is valid and reliable.